Speleothem deposition at the glaciation threshold - an attempt to constrain the age and paleoenvironmental significance of a detrital-rich flowstone sequence from Entrische Kirche Cave (Austria) - Meyer, Michael; Spötl, Christoph; Mangini, Augusto (Palaeogeography, palaeoclimatology, palaeoecology, 2012)
Proxy records from high-altitude locations predating the Last Glacial Maximum are rare but could provide invaluable insights into the response of alpine catchments to the rapid climate fluctuations which characterized the last glacial period. Here we present a detrital-rich flowstone record from Entrische Kirche Cave, an inneralpine cave situated close to the accumulation area of the Pleistocene ice-stream network of the European Alps that expanded repeatedly into the lowlands during glacial maxima. U-Th dating of this calcite is challenging due to high detrital Th. However, petrographic and stable isotope analyses in conjunction with associated clastic cave sediments provide useful insights into the climatic boundary conditions during speleothem formation and into the paleoenvironmental processes which operated in the ~2000m-high catchment above the cave. Our data show that millennial-scale temperature fluctuations had a first-order control on the periglacial activity and vegetation in the catchment which strongly influenced the formation and infiltration of detritus into the karst aquifer. The brown laminated and brown dendritic fabrics that compose much of the detrital-rich flowstone succession reflect these environmental processes. The temperature-dependence of periglacial and permafrost processes allows to constrain the amount of cooling relative to the present-day mean annual air temperature that is required to initiate detrital-rich calcite formation in Entrische Kirche Cave, i.e. −2.5°C (minimum) to −6°C (maximum), respectively. White inclusion-poor calcite that is intercalated with the detrital-rich calcite indicates warm (interstadial) conditions and geomorphological stability in the catchment area. One such phase has been U-Th dated to 88.3±6.9ka (i.e. Greenland Interstadial 21 or 22).